Collaborative Care Management Effectively Promotes Self–Management: Patient Evaluation of Care Management for Depression in Primary Care. Issue 2 (March 2014) - DeJesus, Ramona S.; Howell, Lisa; Williams, Mark; Hathaway, Julie; Vickers, Kristin S.
Abstract: Background: Chronic disease management in the primary care setting increasingly involves self–management support from a nurse care manager. Prior research had shown patient acceptance and willingness to work with care managers.Methods: This survey study evaluated patient–perceived satisfaction with care management and patient opinions on the effectiveness of care management in promoting self–management. Qualitative and quantitative survey responses were collected from 125 patients (79% female; average age 46; 94% Caucasian) enrolled in care management for depression. Qualitative responses were coded with methods of content analysis by 2 independent analysts.Results: Patients were satisfied with depression care management. Patients felt that care management improved their treatment above and beyond other aspects of their depression treatment (mean score, 6.7 [SD, 2]; 10 = Very much), increased their understanding of depression self–management (mean score, 7.2 [SD, 2]; 10 = Very much), and increased the frequency of self–management goal setting (mean score, 6.9 [SD, 3]; 10 = Very much). Predominant qualitative themes emphasized that patients value emotional, motivational, and relational aspects of the care manager relationship. Patients viewed care managers as caring and supportive, helpful in creating accountability for patients and knowledgeable in the area of depression care. Care managers empower patients to take on an active role in depression self–management. Some logistical challenges associated with a telephonic intervention are described.Conclusion: Care manager training should include communication and motivation strategies, specifically self–management education, as these strategies are valued by patients. Barriers to care management, such as scheduling telephone calls, should be addressed in future care management implementation and study.